Potensi Pemanfaatan Gosse (Ceratophyllum Sp) Sebagai Pakan Ternak Itik di Desa Tellumpanua Kabupaten Barru Berbasis Data Citra - Irwan, Muh.; Nugraha, Angga; Mursalat, Aksal; Asra, Reza; Surianti, S (Journal Galung Tropika, 2022)
The duck livestock business is one of the business branches in the livestock sector which is now widely cultivated by the community. Especially in South Sulawesi, duck farming has increased over the last 5 years. This happened because the duck culinary business increased along with the increasing demand and purchasing power of the people. In the aspect of duck farming, the feed factor is one of the problems faced by farmers because the proportion of financing can reach 60-80%. To overcome this, one solution that can be done is to utilize locally available feed ingredients sustainably. Gosse (Ceratophyllum sp) is one type of aquatic plant which if its production is excessive in ponds, can harm the growth of milkfish and shrimp. Its potential is so great, that it is considered very worthy of research. This study aims to determine the potential of Gosse as feed for ducks based on the production of fresh material, dry matter, and carrying capacity based on Geographic Information System (GIS) data. The research method applied includes 4 stages, namely Geographic Information System (GIS) analysis, analysis of fresh and dry matter production, nutritional quality analysis, and production conversion to calculate carrying capacity. The results showed that the production of fresh matter reached 74.7 tons/ha/year and the production of the dry matter reached 4,482 tons/ha/year. The production of gosse in Tellumpanua Village in total reached 1,157.09 tons/year in a fresh state and 70.3674 tons//year in a dry state. Based on these data, the carrying capacity of gosse at 30%, 50%, and 70% use respectively is 270, 162, and 115 head/ha/year or 4239, 2543, and 1805 head/year.